Contribuições à noção de ato na filosofia de Henri Bergson : à luz do Essai sur les données immédiates de la conscience (1889) - Proença, Luiz Fernando de Oliveira (Universidade Federal de São Carlos, 2015)
The aim of this paper is to highlight a particular notion in Bergson’s thought, namely the activity of the mind. Even though this inquiry does not intend to deal with the entire bergsonian corpus, as its subtitle indicates, highlighting the aforementioned notion, together with other structuring conceptual aspects, such as synthesis, continuity, indivisibility, might – as we hope – bring about different outlooks to the reading of Bergson’s works. These concepts are supposed to justify the inquiry inasmuch as they are supposed to demonstrate that the duration of consciousness, the very object of An Essay on the immediate data of consciousness, is a psychic, mind process, and an activity. A fourfold division was established, corresponding to each of the four chapters that compose this paper, in order to achieve our goal. The first three chapters are dedicated to analyzing each of the three chapters in the Essay, aiming at demonstrating in what way those notions happen to be fundamental in the development of that particular work, the means of their respective genesis and unfoldings. Thus, the opening inquiries into the intensity of psychological states focus on the distinction between the quality and the quantity of psychic data, by means of the concept of intensity. Next, the plurality of such data shall be examined by means of the distinction between the concepts of numerical multiplicity and non-numerical multiplicity. Finally, in the third chapter an analysis shall be undertaken of the organization of such data of consciousness, in order to conclude the description of the psychological subject in the previous chapters and, most importantly, in order to demonstrate that the duration of such subject is synthetic, active, indivisible, while at times producing free activity. The final considerations merely reiterate what has been divided throughout the previous chapters, besides giving a brief mention on the extension of the notion of activity in both of Bergson’s following works: Matter and memory and The Creative Evolution.
Keywords: Psicologia; Metafísica; Duração; Espaço; Psychology; Metaphysics; Duration; Space; CIENCIAS HUMANAS::EDUCACAO